Atmospheric electromagnetism: Individual differences in brain electrical response to simulated sferics - Schienle, Anne; Stark, Rudolf; Kulzer, Rainer; Klöpper, René; Vaitl, Dieter (International journal of psychophysiology, 1996)
The living organism is constantly affected by natural electromagnetic influences covering a wide range of frequencies and amplitudes. One of these natural influences is represented by a phenomenon called atmospherics or sferics. Sferics are very weak electromagnetic impulses generated by atmospheric discharges (lightning). With a newly developed simulation system it was possible to reproduce a previously registered sferics signal and present it to 52 subjects while recording the electroencephalogram (EEG). The repeated application of this stimulus for ten minutes evoked a significant decrease in alpha power in parietal and occipital regions compared to the control condition without sferics presentation. Two constitutional factors were revealed as mediators of sferics effectiveness: the general physical condition of the subjects, and their neuroticism. Individuals with many somatic complaints and a high degree of emotional lability did not respond to the sferics stimulation. This absence of a response is interpreted as an adaptational deficit in reaction to variations in atmospheric parameters.